Fungal Contamination of Indoor Public Swimming Pools, Ahwaz, South-west of Iran - A Rafiei; N Amirrajab (Tehran University of Medical Sciences, 2010)
Background: Using public swimming pools during different seasons and poor health behavior could be responsible in transmission of fungal disease through pool water and its environment. Therefore, this research was conducted to investigate fungal agents of indoor public swimming pools of Ahwaz, capital city of Khouzestan Province, south-west of Iran. Methods: Ten indoor swimming pools of Ahwaz were investigated during two seasons for 6 months. Water specimens were collected by pump and environment samples including shower-bath area, margin of pool walls, dressing rooms, and slippers, by sterile carpet pieces. All specimens were cultured in SC and SCC culture media and fungal agents identification were based on macroscopic, microscopic characteristic and complement tests when it was necessary. Data analyzing was performed using SPSS version 13 for descriptive analyzing. Results: A total of 593 samples were collected from different parts of pools. Interestingly in 13 samples from environmental places, dermatophytes were isolated as follows: Trichophyton mentagrophytes, T. rubrum, T. verrucosum and Epidermophyton floccosum 5, 4, 3 and 1 cases respectively. Ten cases of dermatophytes were isolated from floor of dressing area. Three hundred seventy two saprophytic fungi species and 32 yeasts were recovered from water and environment surfaces samples. Aspergillus, Penicillium and Mucor were the most common isolated saprophytic fungi. Conclusion: Existence of saprophytic fungi and yeast in pools water seems to be an indicator of their resistance to detergent agents. In addition, yeast water contamination could be from swimmers. Dermatophytes isolation from pools environment areas and foot washing sink, reveals the importance of public swimming pools in disease transmission. Because dressing places are being used by all of the swimmers, take care of hygienic discipline in these places should be noted by health policy markers.